Modern software review techniques and technologies - Wong, Yuk Kuen, 1973- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
Software quality is vitally important to the success of a business, as a single undetected error or defect during the software development process could have disastrous consequences during a business operation. Software review is one of the methods used to detect defects. This process maintains the quality of the product by reviewing interim deliverables during development. This book provides an understanding of the critical factors affecting software review performance and gives practical guidelines for software reviews.